Molecular architecture of annelid nerve cord supports common origin of nervous system centralization in bilateria - Denes, Alexandru S.; Arendt, Detlev (Cell, 2007)
To elucidate the evolutionary origin of nervous system centralization, we investigated the molecular architecture of the trunk nervous system in the annelid Platynereis dumerilii. Annelids belong to Bilateria, an evolutionary lineage of bilateral animals that also includes vertebrates and insects. Comparing nervous system development in annelids to that of other bilaterians could provide valuable information about the common ancestor of all Bilateria. We find that the Platynereis neuroectoderm is subdivided into longitudinal progenitor domains by partially overlapping expression regions of nk and pax genes. These domains match corresponding domains in the vertebrate neural tube and give rise to conserved neural cell types. As in vertebrates, neural patterning genes are sensitive to Bmp signaling. Our data indicate that this mediolateral architecture was present in the last common bilaterian ancestor and thus support a common origin of nervous system centralization in Bilateria.